Dynamics of water waves over fringing reefs - Siow, Andrea Jia Yi (2014)
Coral reefs occur under an extensive range of physical environments. Waves, tides, wind, and buoyancy determine the flow on such reefs. The dominant driving mechanism varies among different reefs and is a combination of geomorphologic, meteorological and oceanographic forcing condition at specific sites. Granting that winds, tides and buoyancy forcing could individually dominate the hydrodynamic characteristics of some reefs at certain times, wave action is being increasingly acknowledged as a noteworthy agent in determining island formation, various aspects of reef area ecology and in particular, the reef-flat environment. The role of waves as an energy source to the reef ecosystem and as a significant contributor to the stability and growth of coral reefs is becoming more evident as more reef studies are conducted. Waves breaking on a reef generate a radiation stress gradient that brings about wave setup and wave-induced currents. Varying reef profiles (fore-reef slope, reef-flat bathymetry and reef-flat width) and the differing features of the individual incident waves do play a vital role in the hydrodynamics of wave breaking over coral reefs. The objective of this Final Year Project (FYP) is to study the various coastal profiles, their corresponding slopes and the resulting wave dynamics on fringing reefs.